Treatment approaches for FGFR-altered urothelial carcinoma: targeted therapies and immunotherapy - Benjamin, David J.; Hsu, Robert (Frontiers in Immunology, 2023)
The treatment of metastatic urothelial carcinoma has dramatically changed over the past decade with the approval of several therapies from multiple drug classes including immune checkpoint inhibitors, targeted therapies, and antibody drug conjugates. Although next generation sequencing of urothelial carcinoma has revealed multiple recurring mutations, only one targeted therapy has been developed and approved to date. Erdafitinib, a pan-fibroblast growth factor receptor (FGFR) inhibitor, has been approved for treating patients with select FGFR2 and FGFR3 alterations and fusions since 2019. Since then, emerging data has demonstrated efficacy of combining erdafitinib with immunotherapy in treating FGFR-altered urothelial carcinoma. Ongoing trials are evaluating the use of erdafitinib in non-muscle invasive urothelial carcinoma as well as in combination with enfortumab vedotin in the metastatic setting, while other FGFR targeted agents such as infigratinib, AZD4547, rogaratinib and pemigatinib continue to be in development. Future challenges will include strategies to overcome FGFR acquired resistance and efficacy and safety of combination therapies with erdafitinib and other FGFR targeted agents.